Musical activity and emotional competence – a twin study - Theorell, Töres P.; Lennartsson, Anna-Karin; Mosing, Miriam A.; Ullén, Fredrik (Frontiers in Psychology, 2014)
The hypothesis was tested that musical creative achievement and musical practice are associated with lower alexithymia. 8000 Swedish twins aged 27-54 were studied. Alexithymia was assessed using the Toronto Alexithymia Scale (TAS-20). Musical achievement was rated on a 7-graded scale. Participants estimated number of hours of music practice during different ages throughout life. A total life estimation of number of accumulated hours was made. They were also asked about ensemble playing. In addition, twin modelling was used to explore the genetic architecture of the relation between musical practice and alexithymia. Alexithymia was negatively associated with (i) musical creative achievement, (ii) having played a musical instrument as compared to never having played, and – for the subsample of participants that had played an instrument – (iii) total hours of musical training (r = -.12 – in men and -.10 in women). Ensemble playing added significant variance. Twin modelling showed that alexithymia had a moderate heritability of 36% and that the association with musical practice could be explained by shared genetic influences. Associations between musical training and alexithymia remained significant when controlling for education, depression, and intelligence. Musical achievement and musical practice are associated with lower levels of alexithymia in both men and women. Musical engagement thus appears to be associated with higher emotional competence, although effect sizes are small. The association between musical training and alexithymia appears to be entirely genetically mediated, suggesting genetic pleiotropy.